ANALYSIS OF DRY SEASON VEGETABLE PRODUCTION AMONG KIRI DAM USERS IN ADAMAWA STATE, NIGERIA - Robert, K.; Kara, H. A.; Adamu, M. M.; Muhammad, Bala (Journal of Agripreneurship and Sustainable Development, 2021)
This study analysed the dry season vegetable production in the study area with the objective of estimating the profit and factors that affect vegetable production among the users of Kiri Dam. The data used for the study was collected from 120 randomly selected farms during the 2019 dry farming season. Descriptive statistics, farm budgeting and OLS regression analysis were used to analyse the data. The empirical estimates from farm budgeting methodology showed N29,230/ha net farm income and Naira investment return was 0.32. The Double log functional form showed farm size (P<0.1), seeds (P<0.05), fertilizer (P<0.01), age (P<0.05), and education level (P<0.01) had statistically significant effects on the vegetable production of the farmers in the study region. It was concluded that growing vegetables in the study area during the dry season was profitable. Therefore, it was suggested encouraged to educated youth who were not gainfully employed to join vegetable farming in the study area and supplying subsidized farm inputs such as seeds, fertilizer, and agrochemicals so as to lower production costs and increase profit.